The Influence of BYOD on Results of Students' Learning - Livson, Maya (2021)
This work analyzes the influence and efficiency of BYOD for learning students and academic perfection. The relevance of mobile technologies for learning has been substantiated. The influence of BYOD on academic performance of undergraduate students in terms of their test scores and final course marks, as well as on quality of work on selected course projects and on level of satisfaction with the BYOD course, has been experimentally studied. It has been proved that BYOD exerts positive influence on learning and academic achievements of students measured by their academic test scores, by their final marks and quality of their classroom work, as well as that the implementation of BYOD will stimulate and motivate students, thus affecting their level of involvement and creation of independent learning. The experimental results should be used as a guide for persons making decisions as well as for practical specialists in the field of education, especially in the area of BYOD and mobile learning, which will save significant expenses for stationary learning (for instance, concerning desktop computers, projectors, etc.). Scientific novelty of the studies is that the influence of BYOD on academic performance of students in terms of their test scores and final course marks, as well as on quality of students’ work on selected course projects and on level of satisfaction with the BYOD course, has been comprehensively analyzed.